2015
DOI: 10.1371/journal.pone.0133002
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Clinical Features of Early, Treated Parkinson’s Disease

Abstract: IntroductionTo improve our understanding of sex differences in the clinical characteristics of Parkinson’s Disease, we sought to examine differences in the clinical features and disease severity of men and women with early treated Parkinson’s Disease (PD) enrolled in a large-scale clinical trial.MethodsAnalysis was performed of baseline data from the National Institutes of Health Exploratory Trials in Parkinson’s Disease (NET-PD) Long-term Study-1, a randomized, multi-center, double-blind, placebo-controlled s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 39 publications
(46 reference statements)
6
51
1
1
Order By: Relevance
“…The small sex differences in disease severity that we observed could reflect previous treatment differences prior to receipt of care at the study sites (Saunders-Pullman et al, 2011) or the overall older age of women when compared to men in our sample. This finding is supported by the findings by Augustine et al: no differences in disease severity between men and women were observed as part of a large, clinical trial in which individuals were on similar treatment regiments before enrollment and were in the early stages of disease (Augustine et al, 2015). It is also possible that despite similar disease durations, women have a more severe disease course than men.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The small sex differences in disease severity that we observed could reflect previous treatment differences prior to receipt of care at the study sites (Saunders-Pullman et al, 2011) or the overall older age of women when compared to men in our sample. This finding is supported by the findings by Augustine et al: no differences in disease severity between men and women were observed as part of a large, clinical trial in which individuals were on similar treatment regiments before enrollment and were in the early stages of disease (Augustine et al, 2015). It is also possible that despite similar disease durations, women have a more severe disease course than men.…”
Section: Discussionsupporting
confidence: 78%
“…However, results have been conflicting partly due to differences in sample characteristics and sizes, as well as measurement tools used. In a recent, large cross-sectional study of subjects enrolled in a randomized-clinical treatment trial, no significant differences were seen in health-related quality of life or disease severity between men and women (Augustine et al, 2015). However, investigators did find that women performed better on tests of cognitive function than men.…”
mentioning
confidence: 99%
“…In this population‐based study of diabetic patients, we observed a higher risk of PD in female relative to male subjects. In general population studies, PD incidence is a little higher in males, but in diabetic populations, females have higher risk of PD; the mechanisms are not still known. The possible mechanisms may be related to estrogen effects on dopaminergic neurons and pathways in the brain .…”
Section: Discussionmentioning
confidence: 96%
“…For this research, the exclusive use of male rats was chosen due to the greater incidence of this pathological process in men. Additionally, it has been shown that there are significant differences in the survival rate of dopaminergic neurons between male and female rats exposed to a 6‐OHDA infusion, which is a consequence of increased estrogen in females, a well‐recognized neuroprotective factor against dopaminergic depletion, and the increased vulnerability of the nigrostriatal dopaminergic pathway in male rats (Augustine et al, ; Cantuti‐Castelvetri et al, ; Gillies, Pienaar, Vohra, & Qamhawi, ). These factors could have been confounding to our results if we had included female rats in assessment of locomotor recovery.…”
Section: Discussionmentioning
confidence: 99%